Deu no O Globo : Leonel Brizola e a criação do Partido Democrático Trabalhista (1979-1982) - Marcon, Marcelo (2017)
This research aims to understand the newspaper ―O Globo‘s‖‘ speech about the process that culminates on the creation of the ―Partido Democrático Trabalhista‖ (PDT) by Leonel Brizola‘s action. The Rio Grande do Sul‘s former governor returned from exile in 1979, and sought to recreate the ―Partido Trabalhista Brasileiro‖ (PTB), however, the Electoral Tribunal decided to deliver the acronym to Ivete Vargas. Brizola then created PDT, under the influence of the European social democracy, which he had contact during the exile, especially at the Lisbon Meeting in 1979. Thus, the research approaches the trajectory of Brizola since the exile in Portugal, his return in 1979, the legal dispute by the acronym PTB, the creation of PDT, the campaign and also Brizola's election for governor of Rio de Janeiro in 1982. This entire process was researched by the newspaper search source of ―O Globo‖, which is also the object of study on this dissertation. This research aims to answer the following question: How did the newspaper O Globo elaborate its speech on the action of Leonel Brizola in the process of creation of the ―Partido Democrático Trabalhista‖ in the years from 1979 to 1982? To answer, we aims to understand how the newspaper has created it‘s speech, analyzed according to the methodology proposed by Patrick Charaudeau who understands the political speech as a game of masks, which has discursive ways available to the political subject to try to persuade and seduce the interlocutors. The relevance of the research is justified by the importance of interdisciplinary between history and the media, especially in the context of renovation of political history which selects newspapers as a relevant source for historical research, and for the role played by Leonel Brizola and the newspaper O Globo in the process of political opening of the Brazilian military regime and party reorganization, in which labourism, that was outside the Brazilian political scene since 1964, resurfaces and finds resistance from O Globo.